Building a Community-Controlled Economy : The Evangeline Co-operative Experience - Wilkinson, Paul (Community development consultant) (Book collections on Project MUSE., 1996)
This case study focuses on and analyses the formation of four co-operatives in the Evangeline region, a small Acadian community in the southwest part of Prince Edward Island. Defined by the authors as an 'integrated community-controlled economy,' the Evangeline community demonstrates the potential that a network of interrelated co-operatives has for community economic development. More specifically, the authors discuss why some co-operatives succeed while others fail, and propose a model that outlines the element necessary for any comprehensive community economic-development process.Wilkinson and Quarter look at the Evangeline experiment in the context of two seemingly contradictory trends today: globalization and decentralization. They argue that the initiatives undertaken by the Evangeline community fit within the trend toward decentralization and community control. The citizens of the Evangeline region have formed a community-controlled economy, refusing to accept the conventional wisdom that a small community is not viable in a modern economy. The authors suggest that the Evangeline experiment shows that communities which are being marginalized in the modern world can take matters into their own hands and succeed where externally driven development has failed.